2023
DOI: 10.1002/smll.202206228
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation with Nucleic Acid Nanodevices

Abstract: The precise regulation of interactions of specific immunological components is crucial for controllable immunomodulation, yet it remains a great challenge. With the assistance of advanced computer design, programmable nucleic acid nanotechnology enables the customization of synthetic nucleic acid nanodevices with unprecedented geometrical and functional precision, which have shown promising potential for precise immunoengineering. Notably, the inherently immunologic functions of nucleic acids endow these nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 191 publications
(230 reference statements)
0
5
0
Order By: Relevance
“…exDNA can be recognized by receptors on the surface of or within immune cells. Upon recognition, the DNAs ultimately trigger the recruitment of immune cells that elicit immune responses 74 . A recent study suggests that exDNA influences metabolic reprogramming and the differentiation of T regulatory cells, which in turn promotes osteogenic differentiation and calcification 75 .…”
Section: Extracellualr Dna‐induced Pathological Calcification and The...mentioning
confidence: 99%
“…exDNA can be recognized by receptors on the surface of or within immune cells. Upon recognition, the DNAs ultimately trigger the recruitment of immune cells that elicit immune responses 74 . A recent study suggests that exDNA influences metabolic reprogramming and the differentiation of T regulatory cells, which in turn promotes osteogenic differentiation and calcification 75 .…”
Section: Extracellualr Dna‐induced Pathological Calcification and The...mentioning
confidence: 99%
“…14 Discussion of CpG ODNs for the prophylaxis or treatment of tumors, allergies, and infectious diseases can be found in several reviews published in the last decade. [15][16][17][18][19][20][21][22][23] CpG ODNs are known ligands for Toll-like receptor (TLRs)-9 (TLR9), which are loaded within the endosomal compartment in the B cell and plasmacytoid dendritic cell ( pDC) intracellular compartments. [24][25][26] TLRs are a family of pattern recognition receptors composed of a cytoplasmic Toll/interleukin-1 receptor area and an extracellular leucine-rich repeat, connecting through a transmembrane domain.…”
Section: A Brief Insight Into the Mechanism Of Cpg-induced Immune Act...mentioning
confidence: 99%
“…[56][57][58][59] Recent research has indicated that DNA nanocarriers can also be efficiently utilized for CpG delivery. 21,60 In the design of the DNA nanostructures, the secondary structure of CpG ODNs is an important factor influencing the immune response. 5′-Terminal secondary structures showed greater influence on the immunostimulatory activity than those at the 3′-end.…”
Section: Dna Nanostructure-based Cpg Deliverymentioning
confidence: 99%
“…Covalent immobilization of nanomaterials with miRNAs is a promising approach for modulating immune signaling pathways. The utilization of nanomaterials and miRNAs in the formulation of targeted immunotherapies represents an improvement of the limitations of conventional therapy [ 24 , 105 ]. In addition to expanding the therapeutic repertoire, the delivery of miRNAs using nanomaterials is expected to address some of the disadvantages of conventional therapies, such as off-target effects and the development of resistance.…”
Section: Immunomodulatory Strategies In Drug Deliverymentioning
confidence: 99%
“…In summary, IDDSs represent a promising approach to immunomodulatory drug delivery, providing precise targeting, improved efficacy, and enhanced safety. However, ongoing research is essential to fully unlock the potential of revolutionizing disease treatment strategies [ 23 , 24 ]. The safety concerns regarding nanomaterials in immunotherapy are principally related to their unique properties and interactions with biological systems.…”
Section: Introductionmentioning
confidence: 99%